Linkage and association analysis of hyperthyrotropinaemia in an Alpine population reveal two novel loci on chromosomes 3q28-29 and 6q26-27. Issue 8 (20th June 2011) - Volpato, Claudia B; De Grandi, Alessandro; Gögele, Martin; Taliun, Daniel; Fuchsberger, Christian; Facheris, Maurizio F; Minelli, Cosetta; Pattaro, Cristian; Pramstaller, Peter P; Hicks, Andrew A
Abstract : Background: Thyroid hormones have important roles in growth, development and control of metabolism, and their dysregulation can lead to disease. Objectives: To identify genes contributing to hyperthyrotropinaemia. Design, setting, participants: Linkage and association analyses using 1258 individuals from three Alpine villages. Outcome measures: The study applied two different upper limits of the reference range (URR) for serum thyroid stimulating hormone (TSH) values (TSH ≥4.6 mU/l and TSH >3.0 mU/l), along with normal or low fT4 (free thyroxine) values or thyroid medical treatment to define two groups of individuals for analysis: one hyperthyrotropinaemic or high-TSH (H-TSH) (TSH ≥4.6 mU/l) group; and a larger group (TSH >3.0 mU/l) called hyperthyrotropinaemic and upper reference range TSH (H+URR-TSH). Results: Non-parametric genome-wide linkage analysis was performed on pedigrees generated from the two groups. Linkage analysis in the H+URR-TSH group revealed a significant peak on chromosome 3q28-q29 (LOD 3.34) and a suggestive linkage peak on chromosome 6q26-27 (LOD 2.66). Analysis in the smaller hyperthyrotropinaemic (H-TSH) group supported linkage to chromosome 6q26-27. Single SNP and gene based SNP association analyses under the linkage peaks identified the PDE10A and DACT2 genes as candidates at the chromosome 6 locus. Conclusions: PDE10A or DACT2 were identified as candidate genes contributing to hyperthyrotropinaemia (and possibly hypothyroidism) in this sample. Studies in additional populations support association of variants at this locus with TSH values, especially in the PDE10A gene. Genetic linkage in families with hyperthyrotropinaemia suggests the presence of functional variants that contribute to pathological disruption of the hypothalamus–pituitary–thyroid axis.